Mental Strength of Football Players When Matching: Case Study on Village League Teams Karyamukti Village - Fajar Mohammad Ramdani; Asep Angga Permadi; Azhar Ramadhana Sonjaya; Mohd Izwan Shahril (Indonesian Journal of Physical Education and Sport Science)
Study purpose. This study aims to determine the level of mental toughness of players when competing, this is because one aspect of the team's success is that the players have mental toughness.